One Percent Dietary Spirulina (Arthrospira platensis) Improves Color Brightness and Growth Performance in Zebrafish (Danio rerio) - Husenudin Hatmo; Sitti Hilyana; Bagus Dwi Hari Setyono (Journal of Fish Health, 2026)
Spirulina (Arthrospira platensis) is widely used in ornamental fish diets because it contains carotenoids, phycocyanin, protein, vitamins, and other bioactive compounds that may enhance pigmentation and support growth. However, the optimal dietary inclusion level of spirulina for zebrafish (Danio rerio) remains unclear, particularly when colour performance and growth responses are evaluated simultaneously. This study examined the effects of dietary spirulina supplementation on colour performance, growth, and physiological responses in zebrafish. A 30-day feeding trial was conducted using a completely randomized design with four treatments: 0%, 1%, 3%, and 5% spirulina inclusion, each with three replicate aquaria. Data were analyzed using one-way ANOVA, with Welch ANOVA and Kruskal–Wallis tests used to assess result robustness. Dietary spirulina significantly affected RGB brightness, length gain, and weight gain. The most consistent improvement occurred at 1% inclusion. The highest RGB brightness (83.81 ± 2.13), length gain (0.18 ± 0.01 cm), and weight gain (0.15 ± 0.03 g) were recorded in the 1% treatment, which outperformed the control and higher inclusion levels. Total colour score and specific growth rate also tended to peak at 1%, although these responses showed lower statistical stability under non-parametric analysis. Condition factor, survival, and abnormality were not significantly affected by dietary treatment. Overall, 1% dietary spirulina supplementation provided the most effective balance between improved colour appearance and growth performance, while higher inclusion levels did not produce additional benefits under the tested conditions.